Factors Affecting Biomass Growth and Production of Essential Oil from Leaf and Flower of Salvia leucantha Cav. Issue 4 (4th July 2018) - Inderaja, Bagoes M.; Pradhita, Oka; Hanifah, Rahma; Manurung, Robert; Abduh, M. Yusuf
Abstract: This study was conducted to investigate factors affecting biomass growth and production of essential oils from leaf and flower of Salvia leucantha Cav. (Mexican Sage). The light intensity (37-151 μmol.m -2 s -1 ), water input (76-152 ml/day), and concentration of salicylic acid (0-0.5 mM) were varied and the biomass growth was recorded. The essential oils contained in the leaf and flower were extracted using a steam-distillation technique. The yield of essential oil both from flower and leaf varied from 1-2.76 % and 0.36-0.8 % on a dry weight basis, respectively. The productivity of essential oil was estimated in the range of 0.57-3.96 kg/ha.year and 2.26-4.36 kg/ha.year for both leaf and flower. The highest estimated productivity of essential oil (4.36 kg/ha.yr) was obtained when Salvia leucantha was cultivated without any shade net (receiving a light intensity of 301 μmol.m-2s-1) with a water input of 152 ml/day (100 % water field capacity) and sprayed with 0.25 mM salicylic acid on the surface of the flower once a week. The essential oil from both leaf and flower contain aristolane (7.31-16.33 %) which may have a potential application as anti-malaria substance.